Intra-national variation in organizational commitment: evidence from the Chinese context - Gamble, J.; Tian, Amy (Routledge, 2015)
This study demonstrates how organizational commitment can differ at the sub-national level. We develop and test hypotheses based on levels of economic development and related shifts from collectivism to individualism. The data comprise 1017 retail employees drawn from two economically distinctly different parts of China. We find that organizational commitment is higher in ‘less economically developed’ regions. Affective and normative commitment (NC) negatively predicted turnover intentions, whereas continuance commitment related positively to turnover intentions. Unlike earlier findings using Western samples, this study finds the effect of NC on turnover intentions considerably stronger, suggesting that NC is more predictive of turnover intentions. As expected, our results indicate that continuance commitment is more predictive of turnover intentions in the ‘more economically developed’ regions.